Alunos abjetos: etnografia da inclusão numa escola Municipal de Fortaleza - Lima, Valéria Cassandra Oliveira de (2016)
This thesis, part of apprehension category abject student, identified in the public school of Fortaleza, which triggers mechanisms goals in the elimination of school learning conditions of several students. The abject students present the production of corporeality and specific modes of expression, both in the Disabilities Student (DS) as the Troubled Students (TS). It contains forms of social elaborations based on the radicalization of otherness, these types materialize in the exclusion from the school system, and relate to it, either by non-peaceful subjection the production of its abjection, composing forms of resistance, or under stigmatization processes disability . The constitution of this category came from ethnographic effort to understand the school inclusion. Initially this effort comprised the DS figure as a subject of law and the main inclusion agent. The ethnographic exercise of writing the Field Notebooks, however, were made to see the student who for quite some time is eliminated from the school process, both socially and in school métier: learning. It constitutes the category by presenting research partners. In this context, it questions the possibility of political representation category through welfare policies aimed at both get them, how to eliminate them. The central goal of the thesis is to understand the production of social abjections the school, based of the ethnography origin in 2012 – 2013, and discuss the scope of political representation in this category. The concept of abjection of the feminist theories, Judith Butler (2002, 2003, 2007, 2009, 2012, 2013, 2015), Venna Das (1999, 2008) and Debora Polak (2008); the analytical apparatus focuses on the concept of genealogy of Foucault (1995, 2005, 2010, 2011, 2012) and ethnography is based on the model Favret-Saada (2005). The ideation that student is done in interaction with the locus of learning, their peers, the community where they live and the relationship student and faculty. Wanted therefore denote these categories, focusing less on their constitution as problems for the school structure, but understanding them as forms of production of resistance efforts, borderness elasticity and otherness not covered in the regulation standards. The thesis develops understanding of mechanisms for accountability, focused on exercise of citizenship, understood as a dynamic and negotiable process in the body of social interactions.